Intraspecific Variation of Samara Dispersal Traits in the Endangered Tropical Tree Hopea hainanensis (Dipterocarpaceae) - Song, Yao-Bin; Shen-Tu, Xiao-Lu; Dong, Ming (Frontiers in Plant Science, 2020)
Propagule dispersal is a crucial life history stage, which affects population recruitment and regeneration as well as community structure and functions. The windborne process of samara dispersal is affected not only by samara traits and other plant traits, but also by environmental factors. Therefore, studying samara traits related to its dispersal and intraspecific variation in relation to other plant traits and environmental factors could help to understand population distribution and dynamics. Hopea hainanensis, a Dipterocarpaceae tree species dominant in lowland rainforests in Hainan (China) but endangered due to anthropogenic disturbances, is dispersed mainly by wind because of its sepal-winged samara. Here, we measured dispersal-related intraspecific samara traits of H. hainanensis, and analyzed their variation and correlation in relation to plant height, DBH (diameter at breast height), and elevation plant location. Great variations in the samara traits existed, and the variations were larger within than among individuals, which indicated a “bet-hedging” strategy of this species. Plant height, DBH, and elevation explained slight variation in the samara traits. Samara dispersal potential is mainly affected by the samara mass and morphological traits. Samara settling velocity was significantly positively correlated with fruit mass, seed mass, length and width, as well as samara wing loading, and negatively correlated with wing mass ratio, wing area, and wing aspect ratio. Substantial proportions of intraspecific variation in samara dispersal are explained by the samara mass and morphological traits. Natural regeneration with human-aided dispersal is necessary for recovering the H. hainanensis population. This finding contributes to the generalization of trait-based plant ecology, modeling of seed dispersal in tropical forests, and conservation and recovery of rare and endangered species such as H. hainanensis.